TWO-DIMENSIONAL COMPUTATIONAL MODELING OF THE SOIL THERMAL BEHAVIOR DUE TO THE INCIDENCE OF SOLAR RADIATION - Brum, R. S.; Isoldi, L. A.; dos Santos, E. D.; Vaz, J.; Rocha, L. A. O. (Revista de Engenharia Térmica, 2013)
Nowadays, there is a focus on finding sustainable energy sources, as well as, alternatives to rationalize the use of electrical energy. In this sense, the employment of Earth-Air Heat Exchangers (EAHE) is one technique which allows the reduction of energy consumption for climatization of buildings environments. The present study shows the evaluation of a numerical method to estimate the ground thermal potential, allowing its applicability for future thermal design of EAHE. The soil domain is considered twodimensional and a transient solution for the thermal behavior of the soil is obtained. Moreover, a soil surface temperature distribution equation based on experimental data is employed to define the domain boundary conditions. The simulations are performed with a numerical method based on the finite volume method, more precisely using the software FLUENT®. The results presented an excellent agreement with analytical solutions showing the validity and effectiveness of the computational model for prediction of the soil behavior. The numerical results were also confronted with experimental ones predicted into literature and show a good agreement, with a deviation lower than 14%. The main difference is attributed to the duct presence which is taken into account only for the experimental study.